1.
[tex]2x + 7 = 2x + 1 \\ 2x - 2x = 1 - 7 \\ 0 = - 6[/tex]
2.
[tex]x = 8 - 3x \\ x + 3x = 8 \\ 4x = 8 \\ x = 2[/tex]
3.
[tex]2x - 4 = 4x - 2 \\ - 4 + 2 = 4x - 2x \\ 2x = - 2 \\ x = - 1[/tex]
4.
[tex]7 - 2x = 5x + 28 \\ 7 - 28 = 5x + 2x \\ 7x = - 21 \\ x = - 3[/tex]
5.
[tex]8x - 5 = 9x - 5 \\ - 5 + 5 = 9x - 8x \\ x = 0[/tex]
6.
[tex]8x - 10 = 3x + 5 \\ 8x - 3x = 5 + 10 \\ 5x = 15 \\ x = 3[/tex]
7.
[tex]6x = 18 \\ x = 3[/tex]
8.
[tex]9x - 1 = 1 - 3x \\ 9x + 3x = 1 + 1 \\ 12x = 2 \\ x = \frac{2}{12} = \frac{1}{6} [/tex]